Dampak Perubahan Struktur Ekonomi Terhadap Tingkat Kesejahteraan Petani Dan Tenaga Kerja Sektor Pertanian - Petrus Kristriantono; Yuliawati Yuliawati (Jurnal Sosial Ekonomi Pertanian, 2022)
Abstract Economic growth is an indicator of improving people's welfare. The agricultural sector is a source of employment as well as an economic source for most people in South Sumatra. The exchange rate of farmers in South Sumatra from 2012 to 2020 was 110.13 in a row; 110.03; 100.92; 96.87; 94.58; 95.03; 93.62; 90.52; and 95.37. This value shows the level of farmer welfare is still low. The province of South Sumatra needs to fix problems in the basic sectors in the regions, especially the agricultural sector. The purpose of this study is to analyze changes in the economic structure; knowing the impact of changes in economic structure on the absorption of labor in the agricultural sector; and knowing the impact of changes in economic structure on the level of welfare of farmers in South Sumatra Province. The research method used was analytical descriptive analysis and data analysis techniques used were shift share analysis, production structure pattern analysis, and labor absorption share analysis. The data used is secondary data from the Central Statistics Agency. The results showed that the changes in the economic structure in South Sumatra Province were marked by a decrease in the role or contribution of the agricultural sector, on the contrary, the service sector experienced an increase in contribution, and the industrial sector tended to be stable. The impact of changes in economic structure on employment in the agricultural sector in South Sumatra Province is indicated by the accumulation of labor in the agricultural sector due to the slow movement of labor to the service sector or industry. The impact of changes in economic structure on the level of welfare of farmers in South Sumatra can be seen in the farmer's exchange rate which decreased from 110.13 in 2012 to 95.37 in 2020, this value indicates that farmers have a deficit and have a low level of welfare.